Housing use of immigrants and non-permanent residents in ownership and rental markets - Haozhen Zhang; Feng Hou (Economic and Social Reports)
Understanding the housing use of immigrants and non-permanent residents (NPRs) is important for developing effective housing policies and urban planning strategies. Using 2021 Census data, this study estimates housing unit occupancy rates—defined as the number of dwellings per 1,000 people—for immigrants and NPRs.